2022
DOI: 10.1590/1678-9199-jvatitd-2021-0050
|View full text |Cite
|
Sign up to set email alerts
|

Voracity, reaction to stings, and survival of domestic hens when feeding on the yellow scorpion (Tityus serrulatus)

Abstract: Background: Scorpionism is a worldwide problem that has already made thousands of victims, and multi-disciplinary approaches for controlling their populations are to be more successful. Hens are often mentioned as tools for controlling scorpions; however, systematic/experimental behavioral studies are not available. Moreover, there is no systematic information on the effect of scorpion venoms on hens. Using the venomous yellow scorpion Tityus serrulatus, the present study aimed to clarify the following aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(42 reference statements)
1
4
0
1
Order By: Relevance
“…This has been traditionally a common adopted strategy in rural settings, but, with the astonishing increase in the scorpion population in Brazil recently, citizens associations, urban communities, schools, and even city halls are also building urban henhouses as a strategy to cope with scorpion infestations. Indeed, Murayama and colleagues proved that hens are voracious scorpion predators and are also venom-resistant at some extent [ 153 ]. Although hens fit the criteria for being efficient predators to be used in biological control, it must be considered that their life habits did not match the scorpions’, which are nocturnal animals and stay usually hidden, while chickens pack in the open during the day.…”
Section: The Possible Solutionmentioning
confidence: 99%
“…This has been traditionally a common adopted strategy in rural settings, but, with the astonishing increase in the scorpion population in Brazil recently, citizens associations, urban communities, schools, and even city halls are also building urban henhouses as a strategy to cope with scorpion infestations. Indeed, Murayama and colleagues proved that hens are voracious scorpion predators and are also venom-resistant at some extent [ 153 ]. Although hens fit the criteria for being efficient predators to be used in biological control, it must be considered that their life habits did not match the scorpions’, which are nocturnal animals and stay usually hidden, while chickens pack in the open during the day.…”
Section: The Possible Solutionmentioning
confidence: 99%
“…There is also evidence that some predators have potential for biological control: Jared et al [3] have shown that the toad Rhinella icterica is resistant to the venom of T. serrulatus and that it may feed on the scorpion. The domestic hen Gallus gallus domesticus does not stop feeding on individuals of T. serrulatus despite being stung and does not die from stings [4]. An additional method may be the use of pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…The domestic hen Gallus gallus domesticus does not stop feeding on individuals of T . serrulatus despite being stung and does not die from stings [ 4 ]. An additional method may be the use of pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…the literature also mentions biological control(Jared et al, 2020; Brites-Neto et al, 2021;Murayama et al, 2022) and physical control using materials that prevent or hinder the animal entry. The latter has been used since the 1960s, with measures such as coating houses with ceramic and metal plates around the foundation(Mazzotti, 1964 apud Ramsey et al, 2002 …”
mentioning
confidence: 99%
“…Murayama et al, 2022), lagartos, mamíferos, sapos (e.g. Jared et al, 2020) e cobras(Solórzano e Greene, 2012;Dupre, 2020).…”
unclassified